2016
DOI: 10.1038/sc.2016.129
|View full text |Cite
|
Sign up to set email alerts
|

Movement repetitions in physical and occupational therapy during spinal cord injury rehabilitation

Abstract: Study DesignLongitudinal observational study.ObjectiveTo quantify the amount of upper and lower extremity movement repetitions (i.e., voluntary movements as part of a functional task or specific motion) occurring during inpatient spinal cord injury (SCI) physical (PT) and occupational therapy (OT), and examine changes over the inpatient rehabilitation stay.SettingTwo stand-alone inpatient SCI rehabilitation centres.MethodsParticipants103 patients were recruited through consecutive admissions to SCI rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 37 publications
1
47
1
2
Order By: Relevance
“…By itself, LOS is an inadequate way to compare rehabilitation effectiveness, since a longer LOS may reflect inefficiency as much as it indicates increased therapeutic time and a shorter LOS may reflect increased efficiency/intensity or be indicative of cuts in health care provision, as seen in recent decades in the USA [40]. Accounting for the intensity of therapy, at least in terms of time [41] and ideally in terms of therapy content [42], would allow for a true comparison of rehabilitation interventions between countries.…”
Section: Length Of Stay In Rehabilitationmentioning
confidence: 99%
“…By itself, LOS is an inadequate way to compare rehabilitation effectiveness, since a longer LOS may reflect inefficiency as much as it indicates increased therapeutic time and a shorter LOS may reflect increased efficiency/intensity or be indicative of cuts in health care provision, as seen in recent decades in the USA [40]. Accounting for the intensity of therapy, at least in terms of time [41] and ideally in terms of therapy content [42], would allow for a true comparison of rehabilitation interventions between countries.…”
Section: Length Of Stay In Rehabilitationmentioning
confidence: 99%
“…The average number of steps taken was 357 (between 200 and 300 m) per training session. Zbogar et al [24] conducted a similar analysis but observed 561 physical therapy sessions with individuals with SCI. They counted an average of 51 steps, and these steps occurred primarily in patients who were already able to walk.…”
Section: Intensity and Guidancementioning
confidence: 99%
“…Second, we did not attempt to quantify the training dose in terms of repetitions of the task in the FPT + PNSS or CET groups; such a measure may have been valuable for understanding differences in outcomes across subjects. However, undoubtedly, the number of repetitions was substantially higher than has been reported for inpatient rehabilitation wherein the median number of UE task repetitions for patients with tetraplegia is 42, and with 0 repetitions of hand-related activities (5). A third limitation of this study is that we assessed measures of CSE in a subset of participants.…”
Section: Discussionmentioning
confidence: 74%
“…Not surprisingly, this group frequently cites recovery of arm and hand function as the single most important priority in terms of functional restoration (24). Yet inpatient therapy for persons with tetraplegia has little if any focus on restoration of hand function (5), despite the fact that in persons with tetraplegia hand muscle force generation is highly correlated with success or failure in the ability to perform common functional tasks (6). …”
Section: Introductionmentioning
confidence: 99%